UJI BERBAGAI DOSIS DAN FREKUENSI PEMUPUKAN NPK PADA TANAH BERGAMBUT UNTUK MENINGKATKAN PRODUKSI BAWANG MERAH (Allium ascalonicum L.) - Selvia Sutriana (UIR Press, 2018)
ABSTRACT Lack of community interest in cultivating shallot because of the level of soil fertility in peatlands. The use of NPK 16:16:16 according to proper dosage and frequency of fertilization is important in increasing production. The purpose of this study was to determine the effect of various doses and frequency of NPK fertilization on peat soils to increase onion production. The research was carried out in the Faculty of Agriculture UIR experimental garden for 3 months, starting from September to November 2017. The design used was completely factorial 4 x 4, various dose factors were 100, 200, 300, 400 kg/ha, and the frequency of fertilization factors were 1, 2, 3 times. Observations were made on the production parameters namely the number of tubers, tuber diameter, wet weight, dry weight, and the percentage of tuber shrinkage. Observation data were analyzed statistically and presented in tabular form. The results showed that the effect of real interactions on the dry weight of tubers per clump, the best treatment dose was 100 - 400 kg/ha with the fertilizing frequency of 1-3 times. The main effect of NPK fertilizer dose affects tuber diameter, the best treatment dosage is 300 - 400 kg/ha, while fertilizing frequency significantly influences tuber diameter, the best treatment is 3 times fertilization, while on dry tuber weight per clump, the best treatment is 1 and 3 times fertilization. Keywords: Shallot, Dose, Frequency, NPK, Production